Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species

Mycobiota associated with Platypus cylindrus (Coleoptera: Curculionidae, Platypodidae) in cork oak stands of North West Algeria, Africa - Belhoucine, Latifa; Bouhraoua, Rachid T; Meijer, Martin; Houbraken, Jos; Harrak, M Jamal; Samson, Robert A; Equihua-Martinez, Armando; PUJADE-VILLAR, JULI (AFRICAN JOURNAL OF MICROBIOLOGY RESEARCH, 2011)
Platypus cylindrus (Coleoptera: Curculionidae, Platypodidae) is an important insect pest of the cork oak. These beetles maintain symbiotic relationships with many fungi that serve especially as food for the adults and larvae but also intervene in the mechanisms of establishment of the insect by further weakening the host-tree. 270 samples were taken by 3 sources: Galleries (30), mycangia and intestinal contents of male and female insects and intestinal contents of mature larvae (60 each). The results show the presence of 42 species of ambrosia fungi among which 17 are new to this association. The mycetophagy of these beetles is very rich and consisted essentially of Ophiostomatales. Other groups of fungi playing different roles were also isolated: entomopathogenic, antagonistic, saprophytic but especially pathogenic for the tree host. This group consists of many species and their dissemination by the insect and the inoculation in trees may have fatal consequences by accelerating the cycle of declining affected trees. In the present paper, we discuss the fungal species associated to the beetle, identified on the basis of phenotypic characters and ribosomal DNA sequences analysis, and their relationship with P. cylindrus.
Keywords: Ambrosia fungi; Forest of M'sila (Oran-Algeria); Platypus cylindrus; Quercus suber